Pengembangan Media Pembelajaran Interaktif Berbasis Wordwall pada Mata Pelajaran Al-Qur'an Hadist Untuk Meningkatkan Minat Belajar Siswa di Man Seluma Kab. Seluma Provinsi Bengkulu - Desi Wulandari; Andang Sunarto; Husnul Bahri (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
The objectives of the study are: (1) To determine the effectiveness of the validity of Interactive Learning Media Based on Wordwalls in the Al-Qur'an Hadith Subject. (2) To determine the practicality of the Development of Interactive Learning Media Based on Wordwalls in the Al-Qur'an Hadith Subject to Increase Student Learning Interest at MAN Seluma, Bengkulu Province. (3) To determine the effectiveness of Interactive Learning Media Based on Wordwalls in the Al-Qur'an Hadith Subject to Increase Student Learning Interest at MAN Seluma, Bengkulu Province. The type of research used in this study is quantitative research, the research instrument used is a questionnaire, the data analysis technique used is descriptive statistics, basic assumption tests, classical assumption tests, and hypothesis tests using simple linear regression and multiple linear regression, t-test and F-test. Research results (1) The development in the study is interactive learning media based on wordwalls in learning the Al-Qur'an Hadith of class X students of MAN 1 Seluma. The process of interactive learning media based on wordwall uses the type of research and development (R&D) with a model developed by Thiagaranja, namely the 4-D model and modified into 3-D, namely define, design, and develop. The development of learning media based on animated videos after being validated by 3 expert validators, namely media experts, material experts and subject teachers with the results "very valid" to be developed. (2) The practicality of interactive learning media based on wordwalls in the Al Qur'an Hadith subject for class X students of MAN 1 Seluma was stated to be very practical by students at the madrasah which can be seen from the student response test with an average percentage of 94.22% and falls into the criteria "very practical". (3) The effectiveness of interactive learning media based on wordwalls is stated to be effective for use in the learning process. This is evidenced by the interest in learning and the perception of users of learning media. Evidence of learning outcomes can be seen from the results of the pretest before using the media with an average of 71.85. The results of the posttest after using the media obtained.